PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA MATERI EKOSISTIM BIDANG STUDI ILMU PENGETAHUAN ALAM PADA SISWA KELAS VI SDN 005 BANGUN PURBA - ., Suarni (Edu Research, 2017)
When learning Biology in class VI SDN 005 Bangun Purba, Students are less asked and other students did not respond as a result the class is not alive because the stimulus response should be done, it does not exist. Student learning activity is very less because learning does not start from the observation so as to make. Low student learning achievement. The research type is chosen, that is action research, so this research use the action research model from Kemmis and Taggart (in Arikunto, 2002: 83), which is spiral from one cycle to the next. Each cycle includes planning, action, observation, and reflection. Learning with guided discovery learning model with percentage has a positive impact in improving students 'learning achievement which is marked by the improvement of students' learning mastery in every cycle, that is cycle I (54,16%), cycle II (70,20%) and cycle III (88 , 95%).